2019
DOI: 10.3892/mmr.2019.9887
|View full text |Cite
|
Sign up to set email alerts
|

Anti‑inflammatory effects of Dendropanax�morbifera in lipopolysaccharide‑stimulated RAW264.7 macrophages and in an animal model of atopic dermatitis

Abstract: Dendropanax morbifera ( D. morbifera ), known as Dendro, means ‘omnipotent drug’ (Panax), and has been called the panacea tree. Various studies on D. morbifera are currently ongoing, aiming to determine its medicinal uses. The present study investigated the anti-inflammatory effects and underlying mechanism of a natural extract of D. morbifera leaves (DPL) in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…NO is a highly reactive compound produced from L‐arginine by NO synthase and is involved in pathogen defense, signal transduction, vasodilation, and various other physiological functions of the body. However, excessive NO formation intensifies inflammation, resulting in tissue damage, genetic variation, and nerve damage (Choo et al, 2019). As shown in Figure 5a, NO production significantly increased by 1 µg/ml LPS treatment in the negative control (94.84 ± 3.04 µM) and was suppressed by 38% upon treatment with 20 µM indomethacin, compared to the negative control.…”
Section: Resultsmentioning
confidence: 99%
“…NO is a highly reactive compound produced from L‐arginine by NO synthase and is involved in pathogen defense, signal transduction, vasodilation, and various other physiological functions of the body. However, excessive NO formation intensifies inflammation, resulting in tissue damage, genetic variation, and nerve damage (Choo et al, 2019). As shown in Figure 5a, NO production significantly increased by 1 µg/ml LPS treatment in the negative control (94.84 ± 3.04 µM) and was suppressed by 38% upon treatment with 20 µM indomethacin, compared to the negative control.…”
Section: Resultsmentioning
confidence: 99%
“…Further, it was also determined that D. morbifera treatment significantly decreased NF-κB activation in the LPS-stimulated group. However, the activation of IκB-α was not significantly changed [ 17 ]. Other in vitro studies have suggested that D. morbifera extracts have anti-inflammatory activities.…”
Section: Medicinal Uses and Pharmacological Properties Of mentioning
confidence: 99%
“…Indeed, all species but D. morbiferus are native to the tropics of South Korea, predominantly found on Jeju Island [ 12 , 13 , 14 , 15 ]. Most species of the genus Dendropanax is historically important trees that are largely evergreen, and numerous parts of these plant species commonly been used by indigenous peoples to recover from various disorders, atopic dermatitis, asthma, sore throat, anemia, anti-oxidative, viral infections and kidney problems [ 16 , 17 , 18 , 19 ]. The traditional use of Dendropanax species was used for treating inflammatory and arthritis conditions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on changes in the gut microbiome caused by medicinal plants and their effects on the prevention of liver damage are insufficient. Dendropanax morbifera , which belongs to the Araliaceae family, is a medicinal plant that grows on the southern coast of Korea and is known to have various physiological functions such as anti-inflammatory, anti-cancer, anti-diabetic, and immune regulatory effects [ 15 , 16 , 17 , 18 ]. In addition, a previous study conducted by our research team showed that D. morbifera extract, with its maximal antioxidant activity, inhibited liver damage caused by oxidative stress [ 19 ].…”
Section: Introductionmentioning
confidence: 99%